Stress level among nursing students with dysmenorrhea in UiTM Puncak Alam / Nur Amirah Badaruddinn Husny, Nur Athirah Abu Hassan, Nurul Fatihah Rahmat - Badaruddinn Husny, Nur Amirah; Abu Hassan, Nur Athirah; Rahmat, Nurul Fatihah (2016)
Background: Dysmenorrhea is widely recognized as a gynecological in ladies of regenerative age and has an effect on quality of life among them. Objectives: The aim of this study is to determine the stress level among female students in higher learning institution with dysmenorrhea. Method: A cross-sectional study design are used on 126 respondents and using a selfanswered questionnaire of depression, anxiety and stress scale (DASS) to measure the level of stress. Results: Descriptive analysis showed that 87% of the students were experiencing dysmenorrhea and 98% experience stress. This study shows 47.6% (n=60/126) with mean 2.34 (SD=0.792) experience mild pain while 37.3% (n=47/126) with mean 15.254 (SD=4.95380) experience severe stress. It also shows significant between stress and dysmenorrhea (pO.OOl) withr=0.400. Conclusion: This study conclude that students experience worse stress during menstruation with dysmenorrhea and may have an effect on their daily activities and performances.